Design and Building of a Breeding House for IoT-based Goat Farming - Jumi Jumi (JURNAL INFOTEL, 2024)
Abstract — Goat farming is an industry that supplies goat meat for food purposes. This makes goats have a high potential to boost the economy of the community as their meat products are needed by everyone. These conditions motivate farmers to improve the quality of livestock maintenance so that the livestocks produced are of the highest quality. The development of information technology has facilitated a wide range of human activities, including monitoring activities in goat cages. The use of Information Technology helps farmers to improve the quality of livestock maintenance. The large cage area and the distance between cages and communal settlements are the main reasons for the planned IoT-based cage. This research has developed an IoT-based goat cage design that can be used to monitor livestock maintenance in real time via a website or Android. The methods used in this study were cattle identity information, cattle health through body temperature, cage.